Responses of soil bacterial communities and maize yields to sulfur application across four soil types - Dong, Siqi; Zhang, Bing; Wang, Zhao; Zhou, Xue; Gao, Qiang (Frontiers in Microbiology, 2024)
Although the facilitation of sulfur (S) application on maize yield has been well studied, its impact should be validated across soil type and S application rate, and its effect on the soil microbial community structure and function remains unclear. This study aimed to investigate the effects of S application on maize yields and soil bacterial communities in four experimental sites (each site had three S application rates; 0 (S0), 30 (S30) and 90 (S90) kg S ha -1 ), that have different soil types (the soil types were black, sandy, brown and saline). The changeds in soil properties, bacterial community diversity, structure and their contributions to maize production after S application treatments were evaluated. The results showed that 1) S application significantly decreased soil pH, increased soil available sulfur (AS), and increased maize yields in all of the soil types. 2) S application significantly reduced the Chao1 and Shannon diversity index of black soil, but these results were not found in other soils 32) S application significantly affected the bacterial community structure (Except sandy soil) and the abundance of keystone taxaabundance. 43) Black and dark brown soils soil was were more sensitive to S application because their bacterial networks were less complex and it'stheir bacterial community structure wasere less stable. 54) S application had a significant impact on soil physicochemical indicators (such as AS and pH), which mediated bacterial diversity and ultimately led to maize yield regulation, either individually or synergistically. OM (organic matter) (path coefficient = 0.746) had the greatest direct and positive effect on maize yield, followed by AS (0.161) and soil bacterial community diversity (-0.318).Our findings suggest that S application affected soil physicochemical properties and bacterial communities of different soil types. Revealing the underlying mechanism of the above parameters' contributions to maize yield can provide a basis for precision S application.Sulfur (S) was another essential nutrient for plants, following nitrogen (N), phosphorus (P), and potassium (K). It serves as a crucial mineral nutrient, playing a vital role in regulating and controlling plant growth and